2015
DOI: 10.1038/ijosup.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between active school transport and adiposity indicators in school-age children from low-, middle- and high-income countries

Abstract: OBJECTIVES:Within the global context of the nutrition and physical activity transition it is important to determine the relationship between adiposity and active school transport (AST) across different environmental and socio-cultural settings. The present study assessed the association between adiposity (that is, body mass index z-score (BMIz), obesity, percentage body fat (PBF), waist circumference) and AST in 12 country sites, in the International Study of Childhood Obesity, Lifestyle and the Environment (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 37 publications
9
52
2
Order By: Relevance
“…Moreover, 94% of learners walked 15 minutes or less to their transport or from their transport to school. These results are further corroborated by Sarmiento et al, 33 who found that 58% of 10-yearold learners in the Western Cape reported walking to school, and Larouche et al, 34 who found that active school travel was inversely associated with car ownership.…”
Section: School (Physical Education Built and Policy Environments)supporting
confidence: 79%
“…Moreover, 94% of learners walked 15 minutes or less to their transport or from their transport to school. These results are further corroborated by Sarmiento et al, 33 who found that 58% of 10-yearold learners in the Western Cape reported walking to school, and Larouche et al, 34 who found that active school travel was inversely associated with car ownership.…”
Section: School (Physical Education Built and Policy Environments)supporting
confidence: 79%
“…In another study involving 6,797 adolescents aged 9-11 from 12 countries, it was observed those who actively commuted to school had lower BMI values and lower odds of developing abdominal obesity 5 . A survey of 1,570 schoolchildren aged 7-12 years in the city of Joao Pessoa, Brazil, found that excess weight, measured by means of BMI, was higher among passive students (26 % to 32%) or those active for less than ten minutes (25%), in relation to those who actively commuted to school for a time greater than or equal to 10 minutes 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Excess weight (overweight and obesity) when investigated by BMI in adolescents, is directly associated with health problems in adulthood, such as dyslipidemias and cardiovascular diseases (heart failure and heart attack) 1 . Among the strategies for coping with abdominal obesity and excess weight in adolescents, increased levels of physical activity are often investigated 4 , since the performance of physical activity contributes to negative energy balance, favoring the control of fat accumulation in the abdominal region and excess weight 5 . The practice of physical activity can be carried out in several contexts such as school, physical education classes, during school recess or in activities whose objective is to improve muscular strength and endurance 4 .…”
Section: Introductionmentioning
confidence: 99%
“…While active transportation has been associated with increased physical activity, 91 cardiorespiratory fitness, 91 and lower measures of adiposity, 90 evidence suggests that levels of active transportation are declining. [92][93][94][95][96][97][98][99][100] Generational declines in active transportation 101,102 and independent mobility 103 have also been observed.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
“…Multicountry studies have shown similar proportions of active transportation involvement in significantly differing contexts. 89,90 To understand these patterns a "need-based framework" has been proposed for LMIC, where active transportation represents the only option for transportation because motorized vehicle availability remains relatively low in comparison with HIC. The patterns observed in HIC can be understood within a "choice-based framework" where policies and infrastructure facilitate active transportation as an option to commute.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%